Towards Utilising Photocrosslinking of Polydiacetylenes for the Preparation of "Stealth" Upconverting Nanoparticles. (7th November 2018) - Nsubuga, Anne; Zarschler, Kristof; Sgarzi, Massimo; Graham, Bim; Stephan, Holger; Joshi, Tanmaya
Abstract: We demonstrate a novel strategy for preparing hydrophilic upconverting nanoparticles (UCNPs) by harnessing the photocrosslinking ability of diacetylenes. Replacement of the hydrophobic oleate coating on the UCNPs with 10, 12‐pentacosadiynoic acid, followed by overcoating with diacetylene phospholipid and subsequent photocrosslinking under 254 nm irradiation produces water‐dispersible polydiacetylene‐coated UCNPs. These UCNPs resist the formation of a biomolecular corona and show great colloidal stability. Furthermore, amine groups on the diacetylene phospholipid allow for functionalisation of the UCNPs with, for example, radiolabels or targeting moieties. These results demonstrate that this new surface‐coating method has great potential for use in the preparation of UCNPs with improved biocompatibility.